Ulipristal acetate for uterine fibroids: 2 years of real world experience in a UK hospital. (18th August 2018) - Woodhead, Natalie; Pounds, Rachel; Irani, Shirin; Pradhan, Poonam
Abstract: Ulipristal acetate (UPA), is a selective progesterone-receptor modulator, it decreases fibroid size and reduces menstrual bleeding. We reviewed its use at the Heart of England Foundation Trust (HEFT), one of the largest prescribing trusts in the UK. The electronic records of patients treated with UPA from January 2013 to August 2015 were reviewed. One hundred and thirty four patients received UPA, 20 women (15%) received a second course. Eighty percent reported subjective global improvements in symptoms after the first course; 45.5% described amenorrhoea or light bleeding compared to 4.5% prior to treatment. Fewer patients were anaemic (Hb <11 g/dL) following treatment (8.2% versus 33.6%). The majority of fibroids (34%) reduced or remained the same size (25%). Two-thirds of women treated for symptom control avoided surgical intervention. UPA improves symptoms and modifies the use of surgery in treating fibroids. Correcting anaemia prior to major surgery reduces the risk of blood transfusion and optimises a patient's condition as part of an enhanced recovery pathway. Impact Statement: What is already known on this subject: In women with heavy menstrual bleeding secondary to fibroids, UPA has been shown to reduce fibroid size and control uterine bleeding, inducing amenorrhoea in the majority. Initially, only licenced for pre-operative use, an expansion of the licence has included on-going intermittent use for symptomatic fibroids. What the results of this study add: Our review is the largest published cohort of women treated with UPA. It demonstrates symptomatic improvements and advantageous modifications in fibroid size in women of all ethnicities and ages. Our inclusion of women with a uterine size greater than 16 weeks and fibroid diameter larger than 10 cm demonstrates the benefits of UPA with increased fibroid dimensions. What the implications are of these findings for clinical practice and/or further research: These findings can allow clinicians to consider alternative surgical interventions or even avoid surgery completely in a proportion of patients with fibroids. Correcting anaemia and optimising a patient's pre-operative condition reduces post-operative complications and ongoing morbidity. However, 25% of fibroids failed to respond to UPA treatment, further research into the characteristics of women and fibroids that show favourable clinical outcomes will allow identification of those women who are likely to benefit from treatment and prevent futile use in others.